Meningkatkan Kemampuan Mengenal Lambang Bilangan 1-20 Melalui Media Pohon Angka pada Peserta Didik Penyandang Disabilitas Intelektual Ringan - Pinandita, Alya; Rahmahtrisilvia, Rahmahtrisilvia; Damri, Damri; Mahdi, Arisul; Nasri, Yosa Yulia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The problems faced by students with mild intellectual disabilities (MA) and (RP) are their inability to recognize numeral symbols from 1 to 20, which results in suboptimal learning outcomes. This research aims to enhance the ability to recognize numeral symbols from 1-20 through the number tree media for students with mild intellectual disabilities. This study uses the form of classroom action research. Data collection is conducted through observation, documentation, tests, and interviews. The data analysis techniques include data reduction, data presentation, and conclusion drawing. The results of the study show that students' ability to recognize number symbols from 1 to 20 has improved. This is reflected in the initial ability of the students, which was a mean of 30% and a range of 40%. Cycle I shows an increase in the mean (50.8%) and range (58.3%). Cycle II shows further improvement with a mean of (81.2%) and range (83%). Thus, the number tree media can enhance students' ability to recognize number symbols from 1 to 20.